Comparison of various methods of mitigating over pressure induced release events involving ammonia refrigeration using quantitative risk analysis (QRA) - Hodges, Tyler (Kansas State University, 2013)
This project was done to determine the effectiveness of different methods of mitigating the effects of an ammonia release through a pressure relief device in an ammonia refrigeration system. Several methods were considered, and five were selected for further study. The methods chosen for further study were discharge into a tank containing standing water, discharge into the atmosphere, discharge into a flare, discharge into a wet scrubber, and an emergency pressure control system. Discharge into a tank containing standing water is the most common method in existence today but several people in the ammonia refrigeration industry have questioned its reliability. The methods were compared based on a quantitative risk analysis, combining failure rates of each system with ammonia dispersion modeling and the monetized health effects of a system’s failure to contain an ammonia release. It was determined that the release height had a greater influence on the downwind cost impact than any other variable, including weather conditions and release from multiple sources. The discharge into a tank containing standing water was determined to have the lowest failure rate, while the flare system was found to be the most effective in terms of relative overall release consequent cost. The emergency pressure control system is now required by the codes, and any of the other mitigation systems would be very effective when used in conjunction with the emergency pressure control system.
Keywords: Ammonia; Mechanical engineering; Quantitative risk analysis; Mechanical Engineering (0548)